Leiomiosarcoma de Vagina en Paciente Embarazada: Informe de Caso - Piffer, Amanda de Queiroz (2025)
Introduction:Primary malignant lesions of the vagina are atypical, and vaginal sarcomas are even more uncommon. Leiomyosarcomas represent less than 2% of gynecological malignancies, and only 10% of these occur outside the uterus. Case Report: Pregnant woman, 39 years old, sought medical attention due to pain and vaginal bleeding. A pregnant uterus and a solid vaginal mass extending into adjacent fat were found. At the 35th week of gestation, a cesarean section was performed with excision of the tumor, which was subsequently submitted to anatomopathological analysis and diagnosed as vaginal leiomyosarcoma. Conclusion: In this case, tumor removal was the chosen approach, given the presentation of the case, experience of the physicians involved, and availability of the hospital resources where the patient was treated. In fact, there are no specific guidelines for this type of presentation of vaginal leiomyosarcoma, which implies individualization of each case, with different therapeutic approaches, respecting the patient’s particularities.